Co-Working Space in Open Space A Case Study in Green BSD Office Park (Open Space) - Yuamardi, Hadi; Rilatupa, James ED (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Technology and Information are currently growing rapidly and the influence of the lifestyle of the millennial generation has also changed the way we work. One of the changes in this process is that work does not have to be in the office. A study by VMware MeConomy, (2014) revealed that the Gen Y workforce has a mobile mindset, with 79% of respondents working at APJ (the Asia Pacific and Japan) saying they could work anywhere, with response rates working at APJ (85 %). working anywhere (work on the go), followed by the company office and then the coffee shop. The development of co-working spaces in Jabotabek is increasingly mushrooming based on Savills Indonesia's research; the total in Jakarta reaches 120,000 square meters. This change in work procedures that do not only have to be sitting in an office room, allows for the human desire to work in open areas to get a new and interesting atmosphere for activities and collaboration. The author correlates how this co-working design is carried out in an open area because it has similar goals, flexibility, and collaborative nature and form. For this reason, the author wishes to examine the potential and constraints of using open space as a co-working space.